Ventricular Septal Defect in an Octogenarian: A Case Report of VSD Surgical Repair Concomitant with Coronary Artery Bypass and Valvular Surgery - Eiki Tayama; Satoshi Fujita; Tomohiro Ueda; Ken-ich Imasaka; Naofumi Enomoto; Hirofumi Onitsuka; Yukihiro Tomita (Case Reports in Cardiology)
Finding an untreated or asymptomatic large ventricular septal defect (VSD) in an elderly patient is uncommon. The present case was an 81-year-old man who suffered from acute myocardial infarction due to three-vessel coronary disease, mitral and tricuspid valve insufficiency, and high-flow perimembranous VSD (Qp/Qs 2.3). Although the patient was elderly and the VSD had been asymptomatic for a long time, we considered that high-flow VSD and valve diseases should be repaired simultaneously with coronary disease. Then, he underwent elective surgery, namely, VSD patch repair concomitant with coronary artery bypass grafting, and mitral and tricuspid annuloplasty. His postoperative course was uneventful. We conclude that, even for an octogenarian, surgical repair of VSD is recommendable, if surgical indications are appropriate.